Eksplorasi Fraud Intention pada Karyawan Ditinjau dari Status Hubungan Kerja - Nugroho, Muhammad Adi Cokro; Halida, Arfin Nurma (PSIMPHONI, 2024)
Fraud is an action carried out by individuals to seek personal gain at the expense of others. These events lead to large financial losses for the company. This study aims to explore fraud intention among 116 employees based on their employment status. The research employs a quantitative method with a sample of 116 employees positioned as crew store. The participants in this study consist of both contract and permanent employees. The data analysis technique used in this study is descriptive statistical analysis. Fraudulent behavior is difficult to measure; therefore, the instrument in this study uses a development from the theory of planned behavior to measure individual intentions. The results of the study indicate a difference in fraud intention between contract and permanent employees. Overall, the findings show that permanent employees have the highest average scores. Because the measurement of fraud intention in permanent employees is higher than contract employees, therefore, permanent employees have more fraud intention towards the agency than contract employeesKata kunci: fraud, intention to commit fraud, employment status